(untitled) (PerCursos, 2025)
In the Lower Amazon, the species Pterygoplichthys pardalis, popularly known as acari, is one of the ten main species in small-scale commercial fisheries in the region. The objective of this study was to describe and analyze the local ecological knowledge of fishermen regarding the reproductive aspects of acari in the Lower Amazon floodplain. To obtain data, semi-structured interviews were conducted with the fishermen, the script for which consisted of questions that addressed personal aspects, experiences and social relationships of fishing, as well as reproductive aspects of the acari, such as spawning period and location, parental care, among others. Sampling of acari specimens was also carried out for reproductive biology analyses. The fishermen demonstrated that they had refined knowledge about acari reproduction, comparable to the scientific knowledge found in the literature. The fishermen pointed out the acari spawning period starting in the dry season (November) and extending until the flood season (February). This was also evidenced through biological analyses, where 350 gonads of female acari were analyzed, with the highest frequency of mature females observed in the dry period and the highest frequencies of spawned females recorded in the subsequent period (flood). The determination of the reproductive period, through biological analyses, combined with the knowledge of fishermen, suggests the need for adjustments to the official closed season for the acari, with a view to protecting the months of high reproductive intensity of the species. These results contribute to the recognition of the importance of traditional communities and their knowledge, which must be incorporated into the set of technical-scientific information available to support conservationist public policies and regional fisheries management.